Pengaruh komitmen dan disiplin terhadap kepuasan kerja karyawan PT. Wahyuda Abadi Koto Baru - Muhammad Akram; Marzolina '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted at PT. Eternal Wahyuda New Koto Jl. Southern District of New Logas Koto Regency Kuantan Singingi. With the aim to determine the effect of simultaneous commitment and discipline on job satisfaction of employees of PT. Eternal Wahyuda Koto Baru, next to determine the effect of commitment on job satisfaction PT. Eternal Wahyuda New Koto, and to determine the effect on employee job satisfaction discipline PT. Eternal Wahyuda New Koto. In this study population studied were employees of the office of PT. Eternal Wahyuda New Koto totaling 68 people. The sampling method used is the census of 68 employees of PT. Eternal Wahyuda New Koto. Multiple Linear Regression method is to determine the relationship between the dependent variable (Y) with the independent variable (X) is used as the data analysis necessary to first examine the validity and reliability of research data. The results showed that there was a significant effect of both simultaneously and significantly between the variables of commitment and discipline to the job satisfaction of employees of PT. Eternal Wahyuda New Koto. Variabel commitment and discipline is the dominant variable in affecting job satisfaction of employees of PT. Eternal Wahyuda New Koto.Keywords : Commitment , Discipline , Job Satisfaction